Cellular composition of atherosclerotic and uninvolved human aortic subendothelial intima. Light-microscopic study of dissociated aortic cells. - Orekhov, A. N. (1984)
Alcoholic-alkaline dissociation was used in the study of cellular composition of human aorta. Cells were isolated from an uninvolved intima and intima with different types of atherosclerotic lesions: fatty infiltration, fatty streak, and atherosclerotic plaque. In the isolated suspension we evaluated the ratio of four previously described morphologic forms of cells: stellate, elongated, elongated with side processes, and flat cells of irregular shape. It was demonstrated that the quota of stellate cells in an atherosclerotic lesion considerably exceeds that of the normal intima. For elongated cells the opposite is true. The other two cell forms are represented in the uninvolved and atherosclerotic intima in approximately equal proportions. Alteration of the ratio of different morphologic forms occurs because of the fact that the number of cells belonging to different morphologic forms increases disproportionately in the lesion zone. Specifically, the number of stellate cells is increased much more substantially, compared with elongated cells.